ASSESSING TEACHING FACTORY READINESS IN MECHANICAL ENGINEERING EDUCATION USING GOOGLE FORMS TO IMPROVE 21ST CENTURY SKILLS - Hidayatullah, Rachmad Syarifudin; Kurniawan, Wahyu Dwi; Soeryanto, Soeryanto; Wulandari, Ruri Nurul Aeni (STKIP PGRI Tulungagung, 2024)
Teaching Factory (TEFA) is a production-based learning model that aims to align student skills with industry needs. This study analyzes the readiness and implementation of TEFA in the Mechanical Engineering Education Study Program at Surabaya State University to improve 21st-century skills in the digital era. Using a simple random sampling method with 44 respondents, the data were analyzed using Rasch modeling because of its accurate measurement in identifying the level of response suitability. The results show that the educational aspect of TEFA received a very positive response, reflecting the contribution of this program in supporting the development of 21st-century competencies, including critical thinking, communication, collaboration, creativity, character, and civic engagement. Students are trained to think critically and solve real problems so that they are ready to face industry challenges. However, the marketing aspect needs to be improved so that information about TEFA is better known and this program gets more comprehensive support from the community. With a more effective promotion strategy, opportunities for collaboration with external parties can increase, and more students can be involved, strengthening the collaboration and communication aspects of 21st-century competencies. Overall, TEFA not only helps students master technical skills but also strengthens 21st-century competencies that are relevant and applicable in the professional world